2009
DOI: 10.1002/cbic.200900339
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Pactamycin Biosynthesis and Engineered Production of New Pactamycin Analogues

Abstract: Pactamycin is an aminocyclopentitol-derived natural product that has potent antibacterial and antitumor activities. Sequence analysis of an 86 kb continuous region of the chromosome from Streptomyces pactum ATCC 27456 revealed a gene cluster involved in the biosynthesis of pactamycin. Gene inactivation of the Fe-S radical SAM oxidoreductase (ptmC) and the glycosyltransferase (ptmJ), individually abrogated pactamycin biosynthesis; this confirmed the involvement of the ptm gene cluster in pactamycin biosynthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 31 publications
4
101
0
Order By: Relevance
“…The distinguishable peak at 15.8 min is compound 2 as confirmed by its MS and MS2 patterns. This result demonstrates that single/multiple site-directed mutagenesis can be easily performed without going through the complicated multi-step procedures used by other conventional approaches (Blodgett et al, 2007; Ito et al, 2009; Karray et al, 2010). …”
Section: Heterologous Expression and Fine Modification Of Natural mentioning
confidence: 75%
See 1 more Smart Citation
“…The distinguishable peak at 15.8 min is compound 2 as confirmed by its MS and MS2 patterns. This result demonstrates that single/multiple site-directed mutagenesis can be easily performed without going through the complicated multi-step procedures used by other conventional approaches (Blodgett et al, 2007; Ito et al, 2009; Karray et al, 2010). …”
Section: Heterologous Expression and Fine Modification Of Natural mentioning
confidence: 75%
“…Unlike the labor-intensive and time-consuming procedures used in the conventional native host-based methods and heterologous host-based methods (Blodgett et al, 2007; Ito et al, 2009; Karray et al, 2010), DNA assembler only requires adding site-specific mutation(s) into the PCR primers used to generate pathway fragments. As an example, the active sites of the DH domain of AurB will be targeted.…”
Section: Heterologous Expression and Fine Modification Of Natural mentioning
confidence: 99%
“…In most cases, individual enzymes are optimized for incorporation into multi-step synthetic routes, such as in the syntheses of the blockbuster drugs sitagliptin 1 , montelukast 2 , and simvastatin 3 , among others 4 . With less frequency, secondary metabolites, their intermediates, and/or analogs are synthesized via recapitulating and improving existing biosynthetic pathways (for example, artimesinic acid 5 , taxadiene 6 ) or by modifying native pathways (such as, pactamycin 7 , macbecin 8 ). Given the apparent multiplicative benefits of combining biotransformations into pathways, it is notable that de novo multistep engineered biosynthetic pathways for the synthesis of unnatural compounds are quite uncommon (1,2,4-butanetriol 9 , 1,4-butanediol 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 It is known that pactamycin acts by inhibition of the initiation of protein synthesis. 11 Recently, Ito et al 12 isolated de-6-MSA-pactamycin and de-6-MSA-pactamycate from the knockout ptmQ (6-MSA synthase gene) mutant of the pactamycin-and pactamycate-producing strain, Streptomyces pactum; ATCC 27456. This mutant was not able to produce pactamycin and pactamycate, which accumulated the intermediates of pactamycin biosynthesis.…”
mentioning
confidence: 99%
“…a-WM-JG-16.2. Ito et al 12 reported that de-6-MSA-pactamycin showed antibacterial and antitumor activities similar to pactamycin, and they suggested that the 6-MSA moiety of pactamycin is not essential for antibacterial and antitumor activities. However, our data indicate that the 6-MSA moiety in 7-deoxypactamycin increases antiprotozoal activity, as well as decreasing cytotoxicity in human cells, suggesting that the 6-MSA moiety has an important role in both antiprotozoal activity and cytotoxicity.…”
mentioning
confidence: 99%